Biuletyn Informacyjny . aktualności życia publicznego, no. 40, 1980 - for ed. committee Anka Kowalska, Joanna Szczęsna, Seweryn Blumsztajn, Eugeniusz Kloc, Jan Walc, Janusz Przewłocki, Przemysław Cieślak (s.n.], 1980)
Creation and circulation: First issues typewritten and carbon-copied by various persons, also in fragments, there exist xerox copies of the typescript.